Electromagnetic Field Radiation in Matter - Gustavo Fano, Walter; Razzitte, Adrian; Larocca, Patricia (IntechOpen, 2020)
This book is dedicated to the interaction of electromagnetic wave radiation in matter, such as the wave propagation in a plasmonic and conductive state, that are dispersive media. The different measurement methods of electrical properties of soils have been studied using several applications. The experimental results of the thermoelectric properties of a chalcogenide system and the electrical conductivity of molten salts and ionic conduction in electrolyte solutions are discussed. The application of an electric field impulse and its influence on the immune responses of animals by increasing different elements of the immune response is discussed. The electromagnetic radiation transmission through skin samples of pigs of different ages have been measured in order to understand the process of absorption and conversion. The methods and results are covered in the book.